The United States and the Making of Modern Greece : History and Power, 1950-1974 - Miller, James Edward (Book collections on Project MUSE., 2009)
Focusing on one of the most dramatic and controversial periods in modern Greek history and in the history of the Cold War, James Edward Miller provides the first study to employ a wide range of international archives--American, Greek, English, and French--together with foreign language publications to shed light on the role the United States played in Greece between the termination of its civil war in 1949 and Turkey's 1974 invasion of Cyprus. Miller demonstrates how U.S. officials sought, over a period of twenty-five years, to cultivate Greece as a strategic Cold War ally in order to check the s.